Modeling Acidity Dynamics Driven by Tidal–Rainfall Interactions in a Tropical Lowland Irrigation Network - Samuel Harjanto; Endita Prima Ari Pratiwi; Joko Sujono (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2026)
Water acidity is a critical determinant of rice productivity in tidal swamp irrigation systems. In the Terusan Tengah Irrigation Area, irrigation water is characterized by high acidity, conditions that may adversely impact rice cultivation. Although extensive field measurements have confirmed the presence of acid water within the network, observational data alone cannot disentangle how acidity patterns in tidal systems are controlled by tidal advection or generated by rainfall-driven runoff. Therefore, two contrasting hydrological scenarios rain-free and post-rainfall were simulated to isolate the mechanism governing pH dynamics. This study employs conservative hydrodynamic modelling using HEC-RAS, representing pH as hydrogen ion concentration, to investigate shifts in the controlling mechanisms of acidity under two contrasting hydrological conditions: rain-free and rainfall-affected periods. The simulations were designed to distinguish pH responses driven by tidal transport from those triggered by rainfall. Under rain-free conditions, tidal inflow transports acidic water into the primary canal, causing acidity to accumulate near segments underlain by shallow pyrite layers, but pH partially recovers during ebb tide as the acidic mass is flushed seaward. In contrast, after rainfall, runoff-driven acidity converges toward the estuary and persists even during low tide, as elevated water levels and pseudo-tidal retention inhibit flushing and prolong the residence time of acidic water within the network. This behavior reflects a governing-mechanism transition: tides act merely as distributors of existing acidity during dry periods, whereas rainfall initiates acid generation and retention within the network, concentrated near the estuary. These findings enhance the understanding of acidity dynamics in the Terusan Tengah irrigation network—driven by tidal fluctuations and rainfall—and provide an initial basis for developing adaptive operational strategies to mitigate acidity accumulation and its impacts on ecosystems, crop productivity, and local livelihoods.